1994
DOI: 10.1007/bf02675915
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of diglycerides and conjugated fatty acid triglycerides in reverse‐phase chromatography

Abstract: The behavior of conjugated fatty acid triglycerides and diglycerides on revers~phase chromatography was studied. Trieleostearin is a geometric isomer of trilinoleni~ The conjugated double bond arrangement in trieleostearin enhances its hydrophobic interaction with the statienary phase and causes it to be eluted later than trilinolenin. In separation of "critical pairs" ef tri-and diglycerides, diglycerides elute later than triglycerides due to the longer fatty acid constituent. Position isemers of 1,2-and 1,3d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Oils. Triglyceride content was determined by high-performance liquid chromatography (HPLC) as described by Chang et al (8). Fatty acid methyl esters were prepared and determined by gas chromatography according to Conkerton et al (9).…”
Section: Methodsmentioning
confidence: 99%
“…Oils. Triglyceride content was determined by high-performance liquid chromatography (HPLC) as described by Chang et al (8). Fatty acid methyl esters were prepared and determined by gas chromatography according to Conkerton et al (9).…”
Section: Methodsmentioning
confidence: 99%
“…Seeds were excised and hand-shelled, and kernels were immediately frozen in liquid N 2 , then stored at -808C. Tung oil was extracted from kernels according to the method of Chang et al (1994) using a Tissuemizer (Tekmar). The ratio of kernel to petroleum ether was 1 g:10 mL.…”
Section: Plant Materials and Determination Of Seed Oil Contentmentioning
confidence: 99%
“…1a and b). The major peaks in the tung oil standard, in increasing elution times, are trieleostearin, linoleoyl-dieleostearin, a combination of oleoyl-dieleostearin and palmitoyl-dieleostearin, and stearoyl-dieleostearin (12) . Inspection of the UV spectrum from 250-350 nm indicated that the large unretained peak in Figure 1b contained very little eleostearic acid.…”
Section: Resultsmentioning
confidence: 99%